2018
DOI: 10.13057/biodiv/d190446
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous endophyte bacteria ability to control Ralstonia and Fusarium wilt disease on chili pepper

Abstract: Yanti Y, Warnita, Reflin, Busniah M. 2018. Indigenous endophyte bacteria ability to control Ralstonia and Fusarium wiltdisease on chili pepper. Biodiversitas 19: 1532-1538. Bacterial wilt and Fusarium wilt caused by Ralstonia syzigii subsp. indonesiensisand Fusarium oxysporum f.sp. capsici (Foc), respectively are the most damaging vascular pathogens in chili pepper (Capsicum annuumL.) and many other crops limiting their production, worldwide. Various strategies have been developed to control wilt pathogensincl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…The most virulence bacteria (the fastest wilt disease development) was then re-cultured in TZC agar and used for plant disease infection. The pathogen was inoculated on the two weeks old plants by root wounding methods described by Yanti et al (2018a). The roots were cut in 2 sides of the plants using scissors and poured with 10 mL (10 8 CFU/mL) of the R. syzigii subsp.…”
Section: Pathogens Innoculationmentioning
confidence: 99%
“…The most virulence bacteria (the fastest wilt disease development) was then re-cultured in TZC agar and used for plant disease infection. The pathogen was inoculated on the two weeks old plants by root wounding methods described by Yanti et al (2018a). The roots were cut in 2 sides of the plants using scissors and poured with 10 mL (10 8 CFU/mL) of the R. syzigii subsp.…”
Section: Pathogens Innoculationmentioning
confidence: 99%
“…Introduction of Bacillus spp. strains as rhizobacteria showed decrease of disease development time, incidence and severity of Ralstonia wilt diseases (Yanti et al 2018).…”
Section: Resultsmentioning
confidence: 95%
“…2). The biocontrol potential of B. pseudomycoides against bacterial wilt disease has recently been reported by two research groups; Hassan et al (2017) demonstrated the biocontrol activity of rhizospheric B. pseudomycoides against bacterial wilt in tomato plants, and Yanti et al (2018) identified endophytic B. pseudomycoides from chili pepper roots as an effective BCA against the bacterial wilt of chili pepper. Although strain G4L1 was phylogenetically close to B. pseudomycoides, this strain may be distinct from this species because its colony morphology is different from that of B. pseudomycoides.…”
Section: Discussionmentioning
confidence: 99%